A multi-modality approach to identifying primary generalized epilepsy that can mimic focal epilepsy. (3rd June 2015) - Duaa, BM; Ye, A; Doesburg, S; Otsubo, H; Ochi, A
Abstract : Introduction: Evaluating the suitability for surgery in patients with epilepsy requires determining if the epilepsy is focal or generalized. Presurgical workups can indicate focal epilepsy in certain cases of generalized epilepsy (GE). The purpose of this study was to identify distinctive features which characterize patients with primary GE that mimics focal epilepsy. Method: We retrospectively identified 19 children with generalized interictal discharges during scalp video-EEG (SVEEG) and underwent invasive monitoring and/or epilepsy surgery. Two children did not undergo resective surgery due to final diagnosis of primary GE (Group A). Seventeen children underwent a resective surgery (Group B). Scalp video-EEG, MEG, MRI, and intracranial video EEG (IVEEG) were reviewed. Results: On (SVEEG), the frequency of generalized spike-and-waves (GSW) was 3Hz in Group A and 1.5-2.5Hz in Group B. Group A had only absence seizures, whereas 80% in Group B had multiple types of seizures. Both groups had lateralized MEG dipoles. One patient in Group A had a focal MRI abnormality. In Group A, IVEEG showed GSW of 3 Hz frequency with inconsistent leading. In Group B, IVEEG showed consistent localization of ictal and interictal high frequency oscillations. Conclusion: Children with generalized 3 Hz spike-and-waves and only absence seizures may be a contraindication of resective surgery even though some presurgical workup shows focality.